Conflict of laws on the rights of child under the Child Act with preventive laws - Sidhu, Baljit Singh; Kamarudin, Abdul Rani (Malaysian Current Law Journal, 2020)
The principal Act governing the handling of the child in conflict with the law is the Child Act 2001 (“CA 2001”) that came into force in August 2002. The CA 2001 consolidated three former Acts: the Juvenile Courts Act 1947; the Child Protection Act 1999; and the Women and Girls' Protection Act 1973 which also incorporated the Convention on the Rights of Children. The CA 2001 therefore updated and upgraded the rights of children including in matters where they are arrested, investigated or charged with an offence. The question then is whether the CA 2001 provides adequate protection to the child. Further, does the CA 2001 yield to other laws especially preventive laws such as the Dangerous Drugs (Special Preventive Measures) Act 1985 (“DD(SPM)A 1985 and Prevention of Crime Act 1959 (“POCA 1959”)? This Article evaluates not only the weaknesses of the CA 2001 but also how these preventive laws erode the rights of the child under the CA 2001. By getting the whole picture, suggestions can be made on how these laws can be improvised jointly or severally to ensure they work harmoniously or coherently with one another to promote rather than erode the rights of the child.